PERCEPTION OF STUDENTS ON TEACHERS 'PROFESSIONAL COMPETENCY IN VOCATIONAL SCHOOL 1 PADANG PANJANGi 4 - Mayang Yulinarti; Sulastri Sulastri; Nelitawati Nelitawati; Hanif Al Kadri (Universitas Negeri Padang, 2021)
AbstractThis research is motivated by the author’s observations regarding students perceptions of the professional competence of teachers in vocational high school (SMK) Negeri 1 Padang Panjang which shows that the professional competence of teachers is less than optimal. The purpose of this research is to obtain data and information regarding (1) mastering subject matter, (2) mastering subject competency standards, (3) developing learning materials, (4) developing professionalism in a sustainable manner, (5) utilizing and using media tools and Learning Resources. The population of this study was 264 students and the sample size was determined using the Slovin formula at an error rate of 10% with the Stratified Proportional Random Sampling technique of 69 students. The results of the data analysis show that the professional competence of teachers at SMKN 1 Padang Panjang is quite capable with an achievement level of 4.26 with the following explanation (1) mastering subject matter is in the very capable category, namely at 4.68, (2) mastering competency standards Subjects are in the capable category, namely at achievement 4.18, (3) developing learning material is in the capable category, namely at achievement 4.10, (4) developing professionalism continuously is in the capable category, namely at achievement 4.27, (5) ) utilize and use media tools and learning resources are in the capable category, namely the achievement of 4.05.